Social Media Movement and Covid-19 Prevention in Indonesia - Dwi Susanti; Lintang Muliawanti (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
The utilization of social media in distributing the information towards covid-19 pandemi is one of the effort from government and society. The access to information through social media has contribute to the pandemi prevention process by re-posting the pictures about health protocol standard. This study aims to characterize the representation of information from social movements and Covid-19 prevention in Indonesia carried out on Instagram social media in 2020-2021. Using qualitative content analysis, manually fetchingInstagram posts with relevant metadata from a social media influencer account @dr.tirta, a government social media account @kemenkes_ri, and an account initiated by public @pandemitalks. Data was collected from March 2020 to June 2021, with 1123 key content and 164 extracted codes analyzed using thematic analysis. It was found that social media is one of the media relied on by the public in accessing Covid 19 information. The input is divided into three general categories including the information needs of the Indonesian people, community problems during the Covid-19 pandemi, and government regulations and policies. And 15 themes that emerged as outputs included health protocols, care, treatment of covid patients, diet and lifestyle, diagnosis and treatment, criticism, innuendo, pregnant women and children, psychology, wrong behavior and habits, misinformation. wrong, political, economic impact and social and cultural impact. Analysis of Instagram post content during a public health crisis can provide new information and realistic insights in a crisis and identify topics of public interest or concern. What information is gathered in this way can help policymakers identify the most critical issues from a public perspective and utilize the knowledge gained to manage ongoing and future pandemis